2011
DOI: 10.1080/19942060.2011.11015369
|View full text |Cite
|
Sign up to set email alerts
|

Subgrid-Scale Modeling of Turbulent Flow Around Circular Cylinder by Mesh-Free Vortex Method

Abstract: This paper proposes a numerical model for the two-dimensional, incompressible, unsteady, turbulent flow applied to an impulsively started flow around a circular cylinder in the Reynolds number range from 110 4 to 610 5 . A Lagrangian mesh-free vortex method blended with the Large Eddy Simulation theory is employed to simulate the large-scale motion, whereas the turbulent subgrid-scale motion is modeled with an eddy viscosity coefficient, expressed in terms of the Second-Order Velocity Structure Function. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Kozlov et al (2011) [12] simulated 2D flow on circular cylindrical objects for Re ranging from 5 to 200 by applying fast Fourier transforms used to solve the Poisson equation for rectangular networks with complex geometries. Mustto and Bodstien (2011) [13] proposed a numerical model to predict the flow characteristics around a circular cylinder for Re between 10 4 and 6*10 5 using the Lagrangian vortex technique without network in combination with the LES model to simulate motion. Wornom et al (2011) [14] conducted a computational analysis of the flow on a circular cylinder at a subcritical regime with Re up to 2*10 5 using a variational-multiscale LES method.…”
Section: Previous Researchmentioning
confidence: 99%
“…Kozlov et al (2011) [12] simulated 2D flow on circular cylindrical objects for Re ranging from 5 to 200 by applying fast Fourier transforms used to solve the Poisson equation for rectangular networks with complex geometries. Mustto and Bodstien (2011) [13] proposed a numerical model to predict the flow characteristics around a circular cylinder for Re between 10 4 and 6*10 5 using the Lagrangian vortex technique without network in combination with the LES model to simulate motion. Wornom et al (2011) [14] conducted a computational analysis of the flow on a circular cylinder at a subcritical regime with Re up to 2*10 5 using a variational-multiscale LES method.…”
Section: Previous Researchmentioning
confidence: 99%
“…The problem of flow around the objects is one of the classical problems in fluid mechanics (Graf & Yulistiyanto, 1998). Under certain conditions, the boundary layer is separated from the surface of the object, which forms the wake region (Mustto & Bodstein, 2011). At lower values of Reynolds number (Re), this wake region is stably enclosed between the separated streamlines of the free stream (Camarri, Salvetti, & Buresti, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of numerical simulations has also been completed (Ghalandari, Mirzadeh Koohshahi, Mohamadian, Shamshirband, & Chau, 2019;Mosavi, Shamshirband, Salwana, Chau, & Tah, 2019;Ramezanizadeh, Alhuyi Nazari, Ahmadi, & Chau, 2019), mainly focusing on the development of the flow around the object. Even though the existing research publications have rigorously demonstrated various distinctions of flow over circular and square cylinders, the scenario with respect to triangular structures seems to have been less explored (Hines, Thompson, & Lien, 2009;Mustto & Bodstein, 2011;Prasath et al, 2014). There is often a phenomenon in which the fluid flows around a pointed object in the thermal system of nuclear power plants or other engineering applications, which can be regarded as the model of the flow around a triangular prism.…”
Section: Introductionmentioning
confidence: 99%
“…Guidoboni et al (2009) used modern techniques such as laser speed measurement and digital imaging to observe the periodic vortex shedding of the cylinder with Reynolds number Re = 3000-9000, and obtained the vortex shedding frequency. Mustto and Bodstein (2011) proposed a numerical model of two-dimensional incompressible unsteady turbulence applied to a pulsed starting flow around a cylinder with Re from 1×10 4 to 6×10 5 . Rajani et al (2009) simulated the flows around two-dimensional and three-dimensional cylinders.…”
Section: Introductionmentioning
confidence: 99%